Relationship Between Rem Sleep Behavior Disorder and Depression and Anxiety and Night Eating Syndrome: Rem Sleep, Depression, Anxiety, Night Eating Syndrome - Cantürk, Rabia Gamze Yürük; Cömert, Itır Tarı; Uğraş, Seda; Akcan, Gizem; Salkım, Dilek İşlek and Tutkun, Erkut and Yükseloğlu, E.Hülya (Progress in Nutrition, 2021)
The purpose of this study is to reveal the risk of depression and anxiety disorders and night eating syndrome in individuals with REM sleep behavior disorder and to determine the relationship between them. Intermittent awakening from sleep to sleep or accompanied by physical movements that could injure itself is defined as REM sleep behavior disorder. Ethical committee approval of the study taken from T.R. Istanbul Arel University. The sample of the study was analyzed by 47 people from T.R. Ministry of Health Süreyyapaşa Chest Diseases and Chest Surgery Training and Research Hospital, 39 people from T.R. Ministry of Health Sultan Abdul Hamid Khan Training and Research Hospital, 28 people from the T.R. Ministry of Health, Okmeydanı Training and Research Hospital were included in the study. Total of 108 data randomly selected were included in the study as control group. It can be said that the REM sleep behavior disorder was low (13-0=13/3=4,33; 0-4,33: low; 4,34-8,66: intermediate; 8,67-13,00: high). There was a positive and significant relationship between REM sleep behavior disorder scores and anxiety (r = .43; p <.05) and depression (r = .56; p <.05) scores. The participants with high REM sleep behavior disorders have high anxiety and depression symptoms.